2014
DOI: 10.1111/omi.12082
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis in the absence of B cells and specific anti‐bacterial antibody

Abstract: Periodontitis (PD) results from complex interactions between a dysbiotic oral microbiota and a dysregulated host immune response. The inflammatory infiltrate in the gingiva of PD patients includes an abundance of B cells, implicating these cells in the immunopathology. We sought to investigate the role of B cells in PD using a murine model. Wild-type or B-cell-deficient (μMT) mice were orally infected with Porphyromonas gingivalis. One or six weeks following infection, lymphocyte populations in the gingiva and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 47 publications
4
40
0
3
Order By: Relevance
“…Our data implicating B cells in periodontal bone loss in C57BL/6J mice are consistent with an earlier study using a different model of mouse periodontitis (oral gavage) (19). Although the authors associated the absence of B cells with protection from bone loss, they did not monitor the appearance of B cells in WT C57BL/6J mice (19).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our data implicating B cells in periodontal bone loss in C57BL/6J mice are consistent with an earlier study using a different model of mouse periodontitis (oral gavage) (19). Although the authors associated the absence of B cells with protection from bone loss, they did not monitor the appearance of B cells in WT C57BL/6J mice (19).…”
Section: Discussionsupporting
confidence: 92%
“…We first determined the time-course of appearance of B cells/plasma cells in the murine gingiva following initiation of periodontitis. Moreover, in view of conflicting results in the literature (18, 19), we examined whether the B-lineage cells are indeed involved in periodontal bone loss.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In human chronic periodontitis B-lineage cells (B lymphocytes and plasma cells) have been revealed to dominate the inflammatory infiltrate suggesting that these cells play a key role in the associated bone loss (79). This is supported by murine studies in the ligature-induced periodontitis model and the P. gingivalis oral infection model, where reduced bone loss was observed in B cell-deficient mice (μMT) compared to wild-type controls (80,81). Furthermore, antibody neutralization of a proliferation-inducing ligand (APRIL) or B-lymphocyte stimulator (BLys), two cytokines important for the maturation and survival of B cells, diminished the number of B cells in the gingival tissue and inhibited bone loss in wild-type but not in B cell- deficient mice (80).…”
Section: Immune Cells and Bonementioning
confidence: 76%
“…The same study does indicate a role for B cells in pathogeninduced bone loss in obese mice. Oliver-Bell et al (8) detected osteoclastogenic RANKL-expressing gingival B cells and reported that infected WT mice had modest bone loss versus sham-infected WT controls, whereas infected B cell-deficient mice were protected from bone loss. Whereas obesity is known to exacerbate periodontitis, in part by acting on B cells (7), it is not a requirement for B cell involvement, as outlined below.…”
mentioning
confidence: 99%